Computational model of 18650 lithium-ion battery with coupled strain rate and SOC dependencies. (15th June 2016) - Xu, Jun; Liu, Binghe; Wang, Xinyi; Hu, Dayong
Graphical abstract: Highlights: An anisotropic model to describe mechanical behaviors of LIB is established. SOC dependency is included in the mechanical model of the jellyroll. Dynamic effect is considered in the model for LIB. Abstract: Highly nonlinear structures and constituent materials and hazardous experiment situations have resulted in a pressing need for a numerical mechanical model for lithium-ion battery (LIB). However, such a model is still not well established. In this paper, an anisotropic homogeneous model describing the jellyroll and the battery shell is established and validated through compression, indentation, and bending tests at quasi-static loadings. In this model, state-of-charge (SOC) dependency of the LIB is further included through an analogy with the strain-rate effect. Moreover, with consideration of the inertia and strain-rate effects, the anisotropic homogeneous model is extended into the dynamic regime and proven capable of predicting the dynamic response of the LIB using the drop-weight test. The established model may help to predict extreme cases with high SOCs and crashing speeds with an over 135% improved accuracy compared to traditional models. The established coupled strain rate and SOC dependencies of the numerical mechanical model for the LIB aims to provide a solid step toward unraveling and quantifying the complicated problems for research on LIB mechanical integrity.